![\frac{(a+2b) ^{2} }{2(a-4b)}+ \frac{(a-2b) ^{2} }{3(4b-a)}- \frac{6ab+b ^{2} }{2(a-4b)}= \\ = \frac{(a+2b) ^{2} }{2(a-4b)}- \frac{(a-2b) ^{2} }{3(a-4b)}- \frac{6ab+b ^{2} }{2(a-4b)}= \\ = \frac{3(a+2b) ^{2}-2(a-2b) ^{2}-3(6ab+b ^{2})}{6(a-4b)}= \\ =\frac{3a ^{2}+12ab+4b ^{2} -2a^{2}+4ab-4b ^{2}-18ab-3b ^{2})}{6(a-4b)}= \frac{(a+2b) ^{2} }{2(a-4b)}+ \frac{(a-2b) ^{2} }{3(4b-a)}- \frac{6ab+b ^{2} }{2(a-4b)}= \\ = \frac{(a+2b) ^{2} }{2(a-4b)}- \frac{(a-2b) ^{2} }{3(a-4b)}- \frac{6ab+b ^{2} }{2(a-4b)}= \\ = \frac{3(a+2b) ^{2}-2(a-2b) ^{2}-3(6ab+b ^{2})}{6(a-4b)}= \\ =\frac{3a ^{2}+12ab+4b ^{2} -2a^{2}+4ab-4b ^{2}-18ab-3b ^{2})}{6(a-4b)}=](https://tex.z-dn.net/?f=+%5Cfrac%7B%28a%2B2b%29+%5E%7B2%7D+%7D%7B2%28a-4b%29%7D%2B+%5Cfrac%7B%28a-2b%29+%5E%7B2%7D+%7D%7B3%284b-a%29%7D-+%5Cfrac%7B6ab%2Bb+%5E%7B2%7D+%7D%7B2%28a-4b%29%7D%3D+++%5C%5C+%3D+%5Cfrac%7B%28a%2B2b%29+%5E%7B2%7D+%7D%7B2%28a-4b%29%7D-+%5Cfrac%7B%28a-2b%29+%5E%7B2%7D+%7D%7B3%28a-4b%29%7D-+%5Cfrac%7B6ab%2Bb+%5E%7B2%7D+%7D%7B2%28a-4b%29%7D%3D+%5C%5C+%3D+%5Cfrac%7B3%28a%2B2b%29+%5E%7B2%7D-2%28a-2b%29+%5E%7B2%7D-3%286ab%2Bb+%5E%7B2%7D%29%7D%7B6%28a-4b%29%7D%3D++%5C%5C+%3D%5Cfrac%7B3a+%5E%7B2%7D%2B12ab%2B4b+%5E%7B2%7D+-2a%5E%7B2%7D%2B4ab-4b+%5E%7B2%7D-18ab-3b+%5E%7B2%7D%29%7D%7B6%28a-4b%29%7D%3D)
![image](https://tex.z-dn.net/?f=%3D%5Cfrac%7Ba+%5E%7B2%7D-2ab-3b+%5E%7B2%7D%7D%7B6%28a-4b%29%7D++%5B%2Ftex%3Cspan%3E%5D%5C%5C%D0%BF%D1%80%D0%B8+a%3D-7%2F6%2C+b%3D1%2F6+%D0%BF%D0%BE%D0%BB%D1%83%D1%87%D0%B0%D0%B5%D0%BC+%5Btex%5D+%5Cfrac%7B%28-+%5Cfrac%7B7%7D%7B6%7D%29+%5E%7B2%7D-2%5Ccdot%28-+%5Cfrac%7B7%7D%7B6%7D%29%28+%5Cfrac%7B1%7D%7B6%7D%29-3%5Ccdot%28+%5Cfrac%7B1%7D%7B6%7D%29+%7B2%7D%7D%7B6%28-+%5Cfrac%7B7%7D%7B6%7D-4%5Ccdot+%5Cfrac%7B1%7D%7B6%7D+%29+%7D%3D+%5Cfrac%7B+%5Cfrac%7B49%7D%7B46%7D%2B+%5Cfrac%7B14%7D%7B36%7D-+%5Cfrac%7B3%7D%7B36%7D%7D%7B6%5Ccdot%28-+%5Cfrac%7B11%7D%7B6%7D%29+%7D+%3D+%5Cfrac%7B+%5Cfrac%7B60%7D%7B36%7D+%7D%7B-11%7D++%3D-+%5Cfrac%7B10%7D%7B66%7D%3D-+%5Cfrac%7B5%7D%7B33%7D++)
]\\при a=-7/6, b=1/6 получаем [tex] \frac{(- \frac{7}{6}) ^{2}-2\cdot(- \frac{7}{6})( \frac{1}{6})-3\cdot( \frac{1}{6}) {2}}{6(- \frac{7}{6}-4\cdot \frac{1}{6} ) }= \frac{ \frac{49}{46}+ \frac{14}{36}- \frac{3}{36}}{6\cdot(- \frac{11}{6}) } = \frac{ \frac{60}{36} }{-11} =- \frac{10}{66}=- \frac{5}{33} " alt="=\frac{a ^{2}-2ab-3b ^{2}}{6(a-4b)} [/tex
]\\при a=-7/6, b=1/6 получаем [tex] \frac{(- \frac{7}{6}) ^{2}-2\cdot(- \frac{7}{6})( \frac{1}{6})-3\cdot( \frac{1}{6}) {2}}{6(- \frac{7}{6}-4\cdot \frac{1}{6} ) }= \frac{ \frac{49}{46}+ \frac{14}{36}- \frac{3}{36}}{6\cdot(- \frac{11}{6}) } = \frac{ \frac{60}{36} }{-11} =- \frac{10}{66}=- \frac{5}{33} " align="absmiddle" class="latex-formula">